Macrophage Polarization: Remote Switching of Elastic Movement of Decorated Ligand Nanostructures Controls the Adhesion‐Regulated Polarization of Host Macrophages (Adv. Funct. Mater. 21/2021). (24th May 2021) - Thangam, Ramar; Kim, Myeong Soo; Bae, Gunhyu; Kim, Yuri; Kang, Nayeon; Lee, Sungkyu; Jung, Hee Joon; Jang, Jinhyeok; Choi, Hyojun; Li, Na; Kim, Minjin; Park, Sangwoo; et al.
Abstract : In article number 2008698, Young Keun Kim, Heemin Kang, and co‐workers report magnetic switching of the movement of decorated ligand‐presenting nanostructures that regulates the adhesion‐mediated polarization of macrophages in vivo. Remote switching of the downward movement of ligand‐presenting nanostructures facilitates macrophage adhesion‐regulated M2 polarization, which is conversely suppressed by their upward movement.